MBA student's engagement with the proposal process: implications for access - Allison, Gadija (School of Education, 2020)
The research component of the Master of Business Administration (MBA) is often cited by MBA students and graduates as the most daunting and challenging part of the MBA programme. This thesis draws on the tools of Critical Discourse Analysis (CDA) (Fairclough, 1989, 1992, 1993, 1995, 2009) and insights from Academic Literacies to understand how novice researchers on the MBA programme at a South African Business School experience the proposal process which aims to prepare them for the writing of the research proposal and, by extension, the dissertation. The CDA assists in highlighting how students, as novice researchers, are positioned and expected to engage as researchers within a key document, the Dissertation Outline, which outlines the rules that govern the research process at the school. Discourse at the level of text shows how the undertaking of research, as well as assuming a specific researcher identity, is foregrounded through the use of textual features that reflect the values and dominant discourses within the programme and the School. The interview data illustrate how students’ actual experiences of the proposal process sit alongside these valued ways of doing and being that are foregrounded in the official documentation and the ways in which the students’ cultural capital impact their engagement with the process. The students’ interview data indicate how they experienced the proposal process as “challenging”, “anxiety-inducing” and “overwhelming”. This is evident in three main factors which shaped their experiences of the research process: the interlinked process of selecting a topic and securing a suitable supervisor; reconciling professional development goals with the valued types of research which are prioritised within the Research Methods course which forms part of the proposal process; and the impact of forms of cultural capital on their experiences of the proposal process. This results in a situation where the researcher identity which is explicitly foregrounded in the Dissertation Outline is questioned. This study illustrates the ways in which the data problematise the School’s assumptions about students’ levels of preparedness for the research process and, more specifically, for the writing of the proposal. The data highlight the importance of recognising that students’ experiences of the proposal process and challenges therein are not only influenced by academic literacy factors that are directly linked to the writing of the proposal, but also by non-textual factors which precede or happen alongside the writing of the proposal. The data further demonstrate how institutional practices impact on the students’ agency and power in the proposal process. This is due to the fact that while some forms of research are foregrounded as valued types of research in the Dissertation Outline, students’ experiences point to limited support in terms of available instruction and supervision for this type of research. The study’s findings highlight the importance of the nature of support provided to students navigating the transition from workplaces and different disciplinary contexts into the research component of the MBA. Based on the study’s findings, it is important that this support take the form of an ongoing dialogue between stakeholders such as supervisors, lecturers, Academic Support, and the Writing Centre. This would serve to address students’ access at various levels, from the nature of pedagogical practices on key courses such as the Research Methods course and how these function to prepare students, to the extent to which students are able to access and enact the valued ways that come with conducting research on the MBA programme.